Selection of Trusted Organic Food Sellers on Instagram Using Fuzzy Analytic Hierarchy Process - et.al, Ramona Ramli (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The awareness ofa healthy lifestyle, particularly in food intake, has resulted in the visibility of organic food products. Most of the organic food products are local-based and home-grown. The popularity of Social Network Sites (SNSs) opens the opportunity for organic food sellers to educate, promote, and market their products to customers. However, the credibility of organic food sellers remains as barriers for customers to purchase from them. In this study, we investigatethe organic food sellers selection problem, and the Fuzzy Analytic Hierarchy process method is applied to determine the most trusted sellers. Organic food sellers with the highest priority weight will be select as trusted sellers. The results of the study expected to be used by organic food sellers to improve their business operations. At the same time, the results will serve as guidelines for customers to evaluate the trustworthiness of organic food sellers.